If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 3x = 7x + -3 Reorder the terms: 16 + 3x = -3 + 7x Solving 16 + 3x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 16 + 3x + -7x = -3 + 7x + -7x Combine like terms: 3x + -7x = -4x 16 + -4x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 16 + -4x = -3 + 0 16 + -4x = -3 Add '-16' to each side of the equation. 16 + -16 + -4x = -3 + -16 Combine like terms: 16 + -16 = 0 0 + -4x = -3 + -16 -4x = -3 + -16 Combine like terms: -3 + -16 = -19 -4x = -19 Divide each side by '-4'. x = 4.75 Simplifying x = 4.75
| 4x^3+5x^2+2x+16=X+2 | | 10x+15+6x-11=180 | | 3x^2+5x=16 | | 4x^3+5x^2+2x+16= | | 3x*2+5x=16 | | 36=-3(k-6) | | y=-0.05x^2+1.25x | | 3(2x+9)=-15 | | 3(w-11)=15 | | 18z-17z+3=17 | | 10-2r=6 | | -6.8(2p+5)-1.6(4p+6)= | | T=24m-4m^2 | | 16=4(n+1) | | h(-4)=-5 | | ix^2-8x+30=0 | | (7x^4+xy^2)dx+(x^2y+6y^5)dy=0 | | x=172+-3x | | 8(x+6)-24=4(2x+5) | | x=172+3x | | x=172 | | -6t^2+24t+14=t | | 2x-5y=36 | | 2x-17=-17+x+2 | | -(6-(a+1))=9-(5-(2a-3)) | | 10=2(h+2) | | -9x-8=6x+1 | | b-8+2b=15 | | x-8x^3+2=0 | | 4x^2=13x^2-9 | | (19b-7)-9(2b+3)=-6 | | 5=4q-7 |